Functioning and teachings of adaptive logics - Batens, Diderik (Logic and Argumentation, 1996)
This paper concerns some formal systems, viz. adaptive logics, that display a specific flexibility in the meanings of logical terms. Both the flexibility that occurs within the systems and the question as to how we may arrive at such systems is discussed. Both, it is argued, are relevant for bridging the gap between logic and argumentation.